Inter-organizational conflicts: Research overview, challenges, and opportunities. (March 2015) - Lumineau, Fabrice; Eckerd, Stephanie; Handley, Sean
While inter-personal conflicts have attracted much attention from scholars and practitioners over the last two decades, our understanding of inter-organizational conflicts remains limited. This paper critically assesses current literature on inter-organizational conflicts. We first discuss the specific features of conflicts at the inter-organizational level. Second, we provide an overview of both qualitative and quantitative research conducted in the field. Third, we make suggestions for future research on inter-organizational conflicts. We specifically suggest opportunities to develop theoretical bridges with other streams of literature and to build multi-level models of conflict management. We then discuss important empirical issues associated with doing research on conflicts between organizations and provide recommendations to overcome these challenges.